The distribution of functional of a trajectory of a particle executing a random walk in a disordered medium - Shkilev, V.P.; Lobanov, V.V. (Поверхность, 2016)
The problem of finding the distribution of functional of a trajectory of a particle executing a random walk in a disordered medium containing both traps and obstacles is considered. As a model of a disordered medium, the Schirmacher model, which is the combination of the random barriers model and the multiple-trapping model, is used. Forward and backward Feynman-Kac equations with the boundary conditions at discontinuity points are formulated. As an example, the distribution of the residence time in a half-space is obtained. It is shown that the anomalous subdiffusion due to traps and that due to obstacles give very different distributions. Розв'язана задача про знаходження функції розподілу траєкторії частинки, що здійснює випадкові блукання в невпорядкованому середовищі, яке містить як пастки, так і бар'єри. В якості моделі невпорядкованого середовища використана модель Ширмахера, яка є комбінацією моделей випадкових бар'єрів і багаторазового захоплення частинки. Сформульовано прямі і зворотні рівняння Фейнмана-Каца з граничними умовами в точках розриву. Як приклад отримано розподіл часу перебування частинки в півпросторі. Показано, що різні типи аномальної субдифузії, обумовленої пастками і бар'єрами, дають функції розподілу, які сильно розрізняються. Решена задача о нахождении функции распределения траектории частицы, совершающей случайное блуждание в неупорядоченной среде, которая содержит как ловушки, так и барьеры. В качестве модели неупорядоченной среды использована модель Ширмахера, которая представляет собой комбинацию моделей случайных барьеров и многократного захвата частицы. Сформулированы прямые и обратные уравнения Фейнмана-Каца с граничными условиями в точках разрыва. В качестве примера получено распределение времени пребывания частицы в полупространстве. Показано, что различные типы аномальной субдиффузии, обусловленной ловушками и барьерами, дают сильно различающиеся функции распределения.